Improved glucose metabolism by Eragrostis tef potentially through beige adipocyte formation and attenuating adipose tissue inflammation - Lemecha, Mengistu (PLoS One, 2018)
BACKGROUND: Teff is a staple food in Ethiopia that is rich in dietary fiber. Although gaining popularity in Western countries because it is gluten-free, the effects of teff on glucose metabolism remain unknown. AIM: To evaluate the effects of teff on body weight and glucose metabolism compared with an isocaloric diet containing wheat. RESULTS: Mice fed teff weighed approximately 13% less than mice fed wheat (p < 0.05). The teff-based diet improved glucose tolerance compared with the wheat group with normal chow but not with a high-fat diet. Reduced adipose inflammation characterized by lower expression of TNFα, Mcp1, and CD11c, together with higher levels of cecal short chain fatty acids such as acetate, compared with the control diet containing wheat after 14 weeks of dietary treatment. In addition, beige adipocyte formation, characterized by increased expression of Ucp-1 (~7-fold) and Cidea (~3-fold), was observed in the teff groups compared with the wheat group. Moreover, a body-weight matched experiment revealed that teff improved glucose tolerance in a manner independent of body weight reduction after 6 weeks of dietary treatment. Enhanced beige adipocyte formation without improved adipose inflammation in a body-weight matched experiment suggests that the improved glucose metabolism was a consequence of beige adipocyte formation, but not solely through adipose inflammation. However, these differences between teff- and wheat-containing diets were not observed in the high-fat diet group. CONCLUSIONS: Teff improved glucose tolerance likely by promoting beige adipocyte formation and improved adipose inflammation.